Microinjection of Antibody to Mad2 Protein into Mammalian Cells in Mitosis Induces Premature Anaphase - Gorbsky, Gary J. (The Rockefeller University Press, 1998)
In yeast, the Mad2 protein is required for the M phase arrest induced by microtubule inhibitors, but the protein is not essential under normal culture conditions. We tested whether the Mad2 protein participates in regulating the timing of anaphase onset in mammalian cells in the absence of microtubule drugs. When microinjected into living prophase or prometaphase PtK1 cells, anti-Mad2 antibody induced the onset of anaphase prematurely during prometaphase, before the chromosomes had assembled at the metaphase plate. Anti-Mad2 antibody-injected cells completed all aspects of anaphase including chromatid movement to the spindle poles and pole–pole separation. Identical results were obtained when primary human keratinocytes were injected with anti-Mad2 antibody. These studies suggest that Mad2 protein function is essential for the timing of anaphase onset in somatic cells at each mitosis. Thus, in mammalian somatic cells, the spindle checkpoint appears to be a component of the timing mechanism for normal mitosis, blocking anaphase onset until all chromosomes are aligned at the metaphase plate.